Profit sharing and monitoring in partnerships - Huddart, Steven; Liang, Pierre Jinghong (Journal of Accounting and Economics, 2005)
We consider partnerships among risk-averse professionals endowed with (i) a risky and personally-costly production technology and (ii) a personally-costly monitoring technology providing contractible noisy signals about partners’ productive efforts. Partners shirk both production and monitoring tasks because efforts are unobservable. We characterize optimal partnership size, profit shares and incentive payments when every partner performs the same tasks, and show that medium-sized partnerships are dominated by either smaller or larger partnerships. Prohibiting some partners from monitoring increases the incentives for others to monitor. We illustrate how task assignments and incentives interact, leading to improvements in partner welfare.